Chymase inhibition prevents myocardial fibrosis through the attenuation of NOX4‐associated oxidative stress in diabetic hamsters - Maeda, Yasutaka (Blackwell Publishing Ltd, 2012)
Aims/Introduction:  Diabetic cardiomyopathy entails the cardiac injury induced by diabetes, independent of vascular disease or hypertension. Despite numerous experimental studies and clinical trials, the pathogenesis of diabetic cardiomyopathy remains elusive. Here, we report that chymase, an immediate angiotensin II (AngII)‐forming enzyme in humans and hamsters, and NOX4‐induced oxidative stress have pathogenic roles in myocardial fibrosis in diabetic hamsters. Materials and Methods:  Expression of chymase was evaluated in the hearts of streptozotocin (STZ)‐induced diabetic hamsters. The impact of chymase‐specific inhibitors, TEI‐E00548 and TEI‐F00806, on myocardial fibrosis, and increased levels of intracardiac AngII, accumulation of 8‐hydroxy‐2′‐deoxyguanosine (an oxidative stress marker in urine and heart tissue) and expression of heart NOX4 in diabetic hamsters were investigated. Results:  Myocardial chymase expression was markedly upregulated in STZ hamsters in a glucose‐dependent manner. A total of 8 weeks after STZ administration, the diabetic hamsters showed enhanced oxidative stress and NOX4 expression in the heart, in parallel with increased myocardial AngII production. Oral administration of chymase‐specific inhibitors, TEI‐F00806 and TEI‐E00548, normalized heart AngII levels, and completely reversed NOX4‐induced oxidative stress and myocardial fibrosis in STZ‐induced diabetic hamsters, although they did not affect the activity of the systemic renin–angiotensin system or systolic blood pressure. Conclusions:  Chymase inhibition might prevent oxidative stress and diabetic cardiomyopathy at an early stage by reducing local AngII production. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2012.00202.x, 2012)